1999
DOI: 10.1002/(sici)1097-0223(199905)19:5<405::aid-pd552>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

A role for maternal serum screening in detecting chromosomal abnormalities in fetuses with isolated choroid plexus cysts: a prospective multicentre study

Abstract: A prospective multicentre study was performed to identify patients with fetal choroid plexus cysts and examine the association between choroid plexus cysts and chromosome abnormalities in the context of variables such as maternal age, serum triple-screen results, race, other prenatally-identified fetal anomalies and cyst characteristics. A total of 18 437 scans were performed in 5 centres and 257 fetuses were identified with choroid plexus cysts. Outcome was available on 250 patients, and of these, chromosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The general view is that none of these factors have any bearing on the risk (Shields et al, 1996;Perpignano et al, 1992;Peleg and Yankowitz, 1998;Brown et al, 1999). The general view is that none of these factors have any bearing on the risk (Shields et al, 1996;Perpignano et al, 1992;Peleg and Yankowitz, 1998;Brown et al, 1999).…”
Section: Can We Modify the Risk?mentioning
confidence: 99%
See 1 more Smart Citation
“…The general view is that none of these factors have any bearing on the risk (Shields et al, 1996;Perpignano et al, 1992;Peleg and Yankowitz, 1998;Brown et al, 1999). The general view is that none of these factors have any bearing on the risk (Shields et al, 1996;Perpignano et al, 1992;Peleg and Yankowitz, 1998;Brown et al, 1999).…”
Section: Can We Modify the Risk?mentioning
confidence: 99%
“…During the introductory phase of this work, it became clear that these results could be used for the evaluation of risk for trisomy 18 (Palomaki et al, 1995). Authors in more recent large series from the US (Brown et al, 1999;Sullivan et al, 1999), although in selected populations, argue that serum biochemical screening can be a valuable adjunct in counselling, with more selective use of invasive testing in isolated cysts with abnormal biochemistry. Gratton and colleagues (1996) used this approach to determine an age cut off value for offering amniocentesis.…”
Section: Can We Modify the Risk?mentioning
confidence: 99%
“…The first description of choroid plexus cyst (CPC) on antenatal sonogram appeared in 1984 (Nicolaides et al 1986), and soon after its association with trisomy 18 was described (Nava et al 1994;Reinsch 1997). Prenatal karyotyping is recommended when along with choroid plexus cysts other fetal ultrasonographic and/or maternal serum markers abnormalities are found (Sharmony 1997;Leonardi et al 1998;Brown et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Gratton et al (1996) offered age-related risks of trisomy 18 that were modified based on the presence of a CPC and normal multiple-marker screening results. Brown et al (1999) and Sullivan et al (1999) concluded that abnormal serum screening can be used as a discriminator for when to offer amniocentesis for isolated CPC. These approaches are flawed because they fail to consider serum screening results or consider all 'normal' multiple-marker screening results equivalent.…”
Section: Introductionmentioning
confidence: 99%